Evaluation of mineral enriched composts for soil remineralisation and crop nutrition - Sreeja S V (Department of Soil Science and Agricultural Chemistry, College of Agriculture, 2015)
The research work entitled „Evaluation of mineral enriched composts for soil remineralisation and crop nutrition‟ has been carried out at College of Agriculture, Vellayani during 2014-2015,to evaluate mineral enriched composts by monitoring nutrient release pattern under laboratory conditions and to study the effects of enriched composts on soil remineralization and crop nutrition using yardlong bean as test crop. The study consisted of three parts 1) Preparationand analysisof enriched composts 2) Laboratory incubation study and 3) Field experiment. Rock dust, which was used as a nutrient source for enrichment consisted of 57.26 per cent Si, 5.07 per cent Fe2O3, 0.85 per cent P2O5, 3.27 percent K2O, 6.42 per cent CaO, 8.23 per cent MgO etc. Five types of composts enriched with different additives viz. mineral enriched compost (Rock dust 25%), bio enriched compost (composting inoculum 5 g kg-1), bio mineral enriched compost (rock dust 25%+ composting inoculum 5 g kg-1), mineral enriched vermicompost (rock dust 25%) and ordinary compost were prepared and used for investigation. Among the various enriched composts prepared, mineral enriched vermicompost recorded high nutrient content. The C:N of rock dust enriched composts were found to be narrow compared to bio enriched and ordinary compost, which indicated that composting period was reduced by the addition of rock dust. As part of assessing the quality of composts as proposed by Saha and panwar (2009) all the composts were classified under same category of marketable B class ofmedium fertilizing potential and low heavy metal content. The results of incubation study revealed that rock dust enriched composts and rock dust enriched vermicompost in conjunction with PGPR Mix-I resulted in an increase in the available nutrient content and enhanced pH and EC. The pattern of release of available N, Pand K was found maximum at 120th day of incubation. The pattern of solubilization of secondary and micronutrients recorded a gradual increase in the nutrient content. The mineral enriched vermicompost in conjunction with PGPR Mix I resulted in maximum release of almost all the nutrients throughout the incubation period. The result of field experiment revealed that 50% N as mineral enriched vermicompost in conjunction withPGPR Mix I showed best result in all observations when compared to other enriched composts. Among the various biometric observations, days to 50 per cent flowering and LAI were found to be significant. Whereas crop duration, number of harvest and appearance of the product were found non significant. In case of quality parametersand yield and yield attributing characters viz. pod length, pod weight, number of pods per plant, pod yield, bhusa yield and total dry matter production,T11(50% N as mineral enriched vermicompost + PGPR Mix I) was found to be the best. Soil characters like physical, chemical and biological properties after the field experiment were improved by enriched composts application either alone or in conjunction with PGPR Mix I.The nutrient uptake by yardlong bean was significant and T11showed the best performance. Pest and disease incidence were reduced for the plants treated with mineral enriched composts. Highest BC ratio was recorded by T11. Contrast analysis of two groups (different composts with and without PGPR Mix I on 50 % and 75 % N basis) were done with respect to yield and yield attributing characters and qualities of yardlong bean andwere significantly different among groups.The group consisted of 50 % N as different composts with PGPR Mix I were found to be the best. From the above points, it was concluded that rock dust when used as an additive to enrich compost might have reduced the composting period as well as enriched the compost with nutrients. The different composts used for the study were under the Marketable B Class (very good quality). Mineral enriched vermicompost in conjunction with PGPR Mix I has given the best result with respect tonutrient release, yield and yield attributes, nutrient uptake and soil remineralization.It was also found that if mineral enriched vermicompost is used as a nutrient source for yardlong bean, the nutrient requirement can be reduced to half of the recommended dose.